Power made perfect? : is there a Christian politics for the twenty-first century? - Sherratt, Timothy (Cascade Books, 2016)
How would politics be different if Christians acknowledged Jesus Christ as the archetype of all rulers, democratic and nondemocratic? How would our practice of politics change if we recognized the suffering love of Christ as the truest exercise of power? Power Made Perfect? offers a distinctive approach to government and politics. It is important, the author argues, to ask how creation provides guidance for political conduct; for politics to be an exercise in piety; and to approach politics in a fallen world with prudence and not in pursuit of ultimate solutions. But it is even more important.